The impact of cultural heritage on sustainable development of local communities:a case of Great Zimbabwe heritage site - Macheka, Mavis Thokozile (Midlands State University, 2014)
This research study focused on the impact of cultural heritage on sustainable development of local communities. The thrust of the study was to know how Great Zimbabwe heritage site as a cultural resource has effected any development in the local people who lived in its vicinity. What is critically important to underscore is the value of the site to society. The study reveals that cultural heritage has effected sustainable development of local communities living in its vicinity although there are other people who felt that they are left out when it comes to development. The community has derived a number of benefits from the site which are economic, cultural, educational, social and environmental. There is employment creation of the local people which is coupled with community projects as Shona village and Craft Centre which generate revenue to the local communities. This is basically economic empowerment of the local people. There is empowerment of women which led to sustainable development because development experience indicates that the economic empowerment of women frequently results in a multiplier effect with community gains and economic growth. Environmental conservation which has the capacity to benefit future generation is also realised and there is social sustainability through maintenance of cultural values. It should be noted that Great Zimbabwe heritage site is a valuable resource for sustainable development but the communities can fully realise sustainable development if there is involvement of the local communities. It is safe to conclude that listening to the voices of local people should be a starting point in any approach to sustainable development.